Social Media Marketing with Online Services and Perceptions, Changing Customer Preferences of Online Retail SME - Andi Nuryadin; Andi Syahrul Makkuradde; Ashari Ismail; Meldianus Nabas J. Lenas; Andi Irfan; Muh. Rum (Universitas Dharma Wacana, 2022)
Customers often make preferences by looking for the best service for the products they need. Customer preferences are related to the behavior of people who have choices. Online customers often make preferences by looking for the best service for the product they need. SMEs try to keep customer preferences from happening. Preference occurs if there are two choices then someone can choose one of them based on the criteria for the comparison results. Preferences are trying to be prevented by online SMEs, because online consumer services are not only seen as product buyers, but also seen as partners in the needs, desires, and expectations of the products sold by the company. This study raises the theory of Preference by Gossen in Tasman (2009) consumer preferences occur when choices occur, then consumers have high utility, and will reduce their consumption if their utility begins to decrease. This research is exploratory, descriptive, to test hypotheses.Â Survey research with incidental sampling on 150 online small entrepreneurs who were met in the general trading area while shopping. Technical analysis by Ordinary Least Square by Path analysis. The results of this study prove that online service quality does not determine perceptions, and perceptions do not determine consumer preferences. Social media marketing does not determine perceptions, and perceptions do not determine consumer preferences.Â So, consumer preferences do not see anymore perceptions, so it only shows consumer preferences for products and is related to any services and social media.